Rectangular microstrip GPS antenna using metamaterial structure with defected ground structure (DGS) / Akram Arif Ab Rahim - Ab Rahim, Akram Arif (2013)
This thesis proposes the miniaturization and performance increment of a conventional microstrip antenna through the incorporation of Defected Ground Structure (DGS) to a metamaterial substrate. The substrate Rogers RO3003 (Er = 3 and h = 0.75mm) is used to design the antenna, as it is suitable to be applied in Global Positioning System (GPS). The antenna is designed to be applied to the civilian GPS frequency; 1.575 GHz. Hence the parameters signifying the performance of the antenna are return loss, bandwidth, VSWR, total efficiency and gain. The Nicholson-Ross-Weir Method (NRW) is applied to ascertain the double negative properties of the metamaterial substrate. Performance variation will be observed from three antennas; conventional antenna, metamaterial antenna and miniaturized metamaterial antenna. Results obtained show increased performance when substrate gains the double negative properties, despite the antenna's dimension. However, performing miniaturization deteriorates the performance of a metamaterial antenna.